Protein-Energy Malnutrition Exacerbates Stroke-Induced Forelimb Abnormalities and Dampens Neuroinflammation - Alaverdashvili, M.; Caine, S.; Li, X.; Hackett, Mark; Bradley, M.; Nichol, H.; Paterson, P. (2018)
Protein-energy malnutrition (PEM) pre-existing at stroke onset is believed to worsen functional outcome, yet the underlying mechanisms are not fully understood. Since brain inflammation is an important modulator of neurological recovery after stroke, we explored the impact of PEM on neuroinflammation in the acute period in relation to stroke-initiated sensori-motor abnormalities. Adult rats were fed a low-protein (LP) or normal protein (NP) diet for 28 days before inducing photothrombotic stroke (St) in the forelimb region of the motor cortex or sham surgery; the diets continued for 3 days after the stroke. Protein-energy status was assessed by a combination of body weight, food intake, serum acute phase proteins and corticosterone, and liver lipid content. Deficits in motor function were evaluated in the horizontal ladder walking and cylinder tasks at 3 days after stroke. The glial response and brain elemental signature were investigated by immunohistochemistry and micro-X-ray fluorescence imaging, respectively. The LP-fed rats reduced food intake, resulting in PEM. Pre-existing PEM augmented stroke-induced abnormalities in forelimb placement accuracy on the ladder; LP-St rats made more errors (29 ± 8%) than the NP-St rats (15 ± 3%; P < 0.05). This was accompanied by attenuated astrogliosis in the peri-infarct area by 18% and reduced microglia activation by up to 41 and 21% in the peri-infarct area and the infarct rim, respectively (P < 0.05). The LP diet altered the cortical Zn, Ca, and Cl signatures (P < 0.05). Our data suggest that proactive treatment of pre-existing PEM could be essential for optimal post-stroke recovery.